ETIOLOGY, TREATMENT AND PREVENTION OF NECROBACTERIOSIS DISEASE IN FARMS (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
This article provides information on the etiology, pathogenesis, spread, clinical signs, diagnostic methods, recommendations for treatment and prevention of necrobacteriosis, a disease that causes great damage to livestock.